OBLITERATING THE PRECONCEIVED PERCEPTIONS OF MASS MEDIA IN RICHARD WRIGHT’S NATIVE SON AND RALPH ELLISON’S INVISIBLE MAN - Agneshia, A. Rosy; Albert, Anita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Media grabs its place in the cockpit for the safe operation of the aircraft stacked with fragile human cognition. The facade of media exhibits its role as leverage in presenting the communal advancement of contriving, nourishing or hampering the notions of universal solidarity. The cogent strategy of media to helm curiosity on the way to and away from the prominent issues under consideration constantly determines and conditions which affair has to be ignited and which has to be extinguished within the society. This chosen or targeted issue that procures notability holds the main cord in manipulating human thoughts about the social, philosophical and political spin-offs. Whatever might be its form whether print, broadcast, cyberspace or out-of-home; the ramifications of its metamorphosis remain a knotty question since antiquity. Considerable theorists and critics uphold media to be perilous advocacy that is to be tamed intending to achieve egalitarianism. These approaches sort to unearth the forthright and expeditious influence on sustainable or passive readers and audiences which gets manifested by the ‘magic bullet theory.’ This article peregrinates through the underrepresentation of the marginalized groups and to be specific the stereotypical depiction of blacks by the media and its dire consequences that electrocute the white minds to capsize the interracial bonds. Richard Wright’s Native Son and Ralph Ellison’s Invisible Man disclose the aspects and various forms of media that throws their claws upon a specific race. On exhibiting such realities, this article tries to bring into existence this long-shrouded motive behind the stereotypical fabrication of the white psyche.